Genetic engineering - Herring, Mark Y., 1952- (Historical guides to controversial issues in America., 2006)
"Genetic engineering has quickly become one of the more controversial issues of our time. Herring provides a detailed history of the debate in a fair and balanced manner, using proponents' points of view to make individual cases, both pro and con. Narrative chapters cover such topics as the Human Genome Project, gene splicing, cloning, genetically altered foods, and DNA and crime-solving. Students and the general public will find a comprehensive survey of the genetic engineering debate. Appendices include statements from Robert P. George and Peter Singer, two of the most prominent scholars on the subject, and a bibliography of print and electronic resources for further research."--Publisher's description.